Effect of Locus of Control and Professional Ethics on Teachers' Performance at University Level - Khalida Parveen; Dr. Wajiha Kanwal; Sabiha Bibi; M. Shahroze Siddiqui (Journal of Management Practices, Humanities and Social Sciences, 2021)
The study was conducted to determine of Locus of Control (LOC) and Professional Ethics (PE) on teachers' performance at university level. The study objectives are to identify the effect of LOC and PE on teachers' performance at university level & find out the relationship between LOC and PE on teachers’ performance at university level. The area of population was delimited to public and private university teachers in Rawalpindi and Islamabad. The study was descriptive and quantitative in nature. Questionnaire was used to determine the effect of LOC and PE on performance of teachers. The sample of the study was taken from ten universities out of twenty-seven universities in the Rawalpindi and Islamabad areas. Universities were selected on the bases of convenient sampling techniques. Data was collected online using Google forms, and researchers personally visited universities to make sure that all questionnaires were filled correctly and on time by the respondent. Findings of the research indicated that internal LOC and PE serve as significant components of teachers' performance. It also showed that PE is the leading variable to affect the performance of teachers.